Formation of FeMo2B2 phase in boron containing 9Cr-1.5Mo ferritic steels - Jung Woo-Sang; Hong Suk-Woo; Song Sang-Min; Kwun, Sook-In; Chung Soon-Hyo (NONFERROUS METALS SOC CHINA, 2006)
The segregation and diffusion of boron during heat treatments were studied. The influence of boron contents, aging time and applied stress on FeMo2B2 formation was also studied. Finally, the effects of boron contents and FeMo2B2 formation on the high temperature strength were studied. Boron. atoms were segregated to prior austenite grain boundary during normalizing treatment. And these boron atoms were slowly diffused into the grain interior during tempering and aging at 700 degrees C. The FeMo2B2 phase was only formed after 1, 000 h aging at 700 degrees C in alloy containing 196 ppm boron. The formation of FeMo2B2 phase is accelerated by the applied stress. It was expected that the formation of FeMo2B2 is closely related to the redistribution of boron atoms. The tensile strengths at 700 degrees C are increased with the increase of boron contents. However, the formation of FeMo2B2 phase results in lower tensile strength.
Keywords: GRAIN-BOUNDARY SEGREGATION; AUSTENITIC STAINLESS-STEEL; NONEQUILIBRIUM SEGREGATION; HIGH-TEMPERATURE; BEHAVIOR; MICROSTRUCTURE; SOLUTE; CREEP